Eristalotabanus violaceus Kröber (Diptera: Tabanidae) a poorly known specie - Buestán A. , Jaime J. (Revista Universidad de Guayaquil, 2013)
For the first time describes the male Eristalotabanus violaceus, based on 34 specimens, species collected in the villages of Tiquibuzo (Chillanes) Bolivar Province at 2350 masl, in the Cordillera Occidental and two specimens collected in Maylas (Azuay) in the Cordillera Oriental. E. violaceus is above 2000 m. altitude. Here it occupes scrublands, forest and Andean highlands, as well as pine plantations. Illustrates the structures of the male compared to the female, also including chart of collecting localities and other species that share the habitat in the Andes of Ecuador
Keywords: Diptera; Tabanidae; Andes; Neotropics Regions; the Male; description; Eristalotabanus violaceus